Scholtzia kalbarri, a replacing name for Scholtzia denticulata (Myrtaceae: Chamelaucieae) - Deshmukh, Umakant Bhoopati (Phytotaxa, 2021)
The Western Australian genus Scholtzia Schauer (1843: 241), is one of the larger genera in the tribe Chamelaucieae of family Myrtaceae with more than 40 species, chiefly found from Carnarvon south to near Harvey and inland to Anderson Rocks, north of Hyden, northern sand plains of the South West Botanical Province and Kalbarri National Park (Rye, 2019). Recently Rye (2019), described twenty-five new species and five new subspecies. One newly described species, Scholtzia denticulata Rye (2019: 55) is illegitimate as it is a later homonym of Scholtzia denticulata F. Mueller (1864: 75).Therefore, a new replacement name is proposed here in accordance with article 53.1 of Shenzhen Code (Turland et al. 2018).